Experimental study on roller compacted asphalt concrete core wall considering the influence of different paving thickness - Hu, Liwen; Li, Zhi; Lin, Shangjie; Sun, Weiqi; Ge, Jianrui; Huang, Ankang; Yuan, Yuncheng (Frontiers in Built Environment, 2025)
Roller compacted asphalt concrete impervious core wall is widely used in water conservancy and hydropower projects because of its excellent anti-seepage, deformation adaptation and seismic performance. The current specification stipulates that the thickness of single-layer paving is 30 cm and 25 cm after compaction, which limits the construction efficiency and economy. In order to break through this limitation, this study relies on the Hongshuihe Reservoir Project in Suzhou District of Jiuquan City to explore the feasibility of increasing the paving thickness to 38 cm and above. Through the field layered paving test, the influence of three different rolling times on the compactness, permeability and mechanical properties of asphalt concrete is studied. The density, permeability coefficient and tensile, compressive and flexural properties were measured by using non-destructive testing and core sample testing methods, and the interlayer bonding quality and construction economy were analyzed. The test shows that the physical and mechanical properties of asphalt concrete meet the requirements of design specifications under the condition of paving thickness of 38 cm. The increase of rolling times significantly optimizes the density and permeability coefficient. The tensile strength, compressive strength and bending resistance of the material can reach the standard index. The bonding quality between the layers is good, and the appearance of the core sample has no obvious delamination trace. Compared with the current 30 cm thickness scheme, the thickness of 38 cm can reduce the number of construction layers by about 69 layers, save the construction period by 35 days and reduce the construction cost by about 628,400 yuan. The research confirms that it is feasible to increase the paving thickness of asphalt concrete to 38 cm under the existing equipment and process conditions, and the construction efficiency and economy are significantly improved. The influence of different rolling times on the performance index is clear, and the optimization of the second rolling times can ensure the paving quality and engineering safety. This study provides important data support and reference for the construction technology optimization and specification revision of roller compacted asphalt concrete core wall.